Contribution of NMR spectroscopy to the mechanistic understanding of photochromism - S. Delbaere; J. C. Micheau; J. Berthet; G. Vermeersch (International Journal of Photoenergy)
Along with classical UV-Visible spectroscopy allowing for the determination of intrinsic properties (λmax,ε), multinuclear NMR spectroscopy is a promising and useful tool for studying photochromic reactions. UV irradiation of the initial structure leads to the formation of photoproducts, which can be structurally identified by 1D and 2D NMR experiments. The kinetics of thermal back reaction are monitored by directly and separately measuring the concentrations of each long-living species at regular time intervals in NMR spectra. A plausible reaction mechanism can therefore be proposed. Based on this mechanism, the kinetic analysis and the study of the effects of temperature lead to the determination of the kinetic and thermodynamic parameters (rate coefficients, enthalpy and entropy of activation) of the photochromic system under investigation. This process has been applied to several photochromic families, spirooxazines and benzo- and naphtho-pyrans.